Peran Kepuasan Kerja sebagai Variabel Mediasi Pengaruh Kecerdasan Emosional dan Kepemimpinan Inklusif terhadap Kinerja Karyawan Rumah Sakit - Salsabila Tama Rosita; Alfato Yusnar Kharismasyah; Wida Purwidianti; Hermin Endratno (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of emotional intelligence and inclusive leadership on employee performance, with job satisfaction serving as a mediating variable, at Ananda General Hospital (RSU) Purwokerto. A quantitative research approach was employed, utilizing purposive sampling to select 155 non-managerial employee respondents. Data were analyzed using Structural Equation Modeling (SEM-PLS). The results indicate that emotional intelligence has a positive and significant effect on both employee performance and job satisfaction. Inclusive leadership has a positive and significant effect on job satisfaction but does not directly and significantly affect employee performance. Furthermore, job satisfaction does not significantly influence employee performance and fails to mediate the effects of the two independent variables. This implies that employee performance at RSU Ananda Purwokerto is driven more by individual emotional intelligence and professional standards than by personal satisfaction or inclusive leadership styles.